Day 3 Wed, November 11, 2015 2015
DOI: 10.2118/177709-ms
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Water Saturation in a Low-Resistivity Pay Carbonate Reservoir Onshore Abu Dhabi: An Integrated Approach

Abstract: Characterization and fluid quantification of Carbonate reservoirs looks more challenging than those of sandstone reservoirs. The determination of accurate hydrocarbon saturation is more tasking due to their complex and heterogeneous pore structures, and mineralogy. Traditionally, resistivity logs are used to identify pay intervals due to the resistivity contrast between oil and water. However, when pay intervals exhibit low resistivity, such logs exhibit low confidence in the precise determination of the hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The nanofluid, which is a dispersion of NPs in base fluids, exhibits higher thermophysical properties like thermal diffusivity, thermal conductivity, and viscosity than its base fluid . The quantification of these fluid properties in porous materials is highly challenging. , The variation in the properties of nanofluids has increased its application in various sectors of oil and gas. , The injection of NPs into the reservoir does not only improve the fluid–rock interactions but also the fluid–fluid interactions . The interfacial and the rheological properties of fluids are altered by the introduction of NPs to the reservoir. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nanofluid, which is a dispersion of NPs in base fluids, exhibits higher thermophysical properties like thermal diffusivity, thermal conductivity, and viscosity than its base fluid . The quantification of these fluid properties in porous materials is highly challenging. , The variation in the properties of nanofluids has increased its application in various sectors of oil and gas. , The injection of NPs into the reservoir does not only improve the fluid–rock interactions but also the fluid–fluid interactions . The interfacial and the rheological properties of fluids are altered by the introduction of NPs to the reservoir. …”
Section: Introductionmentioning
confidence: 99%
“…2 The quantification of these fluid properties in porous materials is highly challenging. 3,4 The variation in the properties of nanofluids has increased its application in various sectors of oil and gas. 5,6 The injection of NPs into the reservoir does not only improve the fluid−rock interactions but also the fluid−fluid interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5 shows the porosity and permeability distributions of rock types in reservoir. Uchida et al (2015) and Ashqar et al (2016) discussed the factors that should be considered when classifying rock type for reservoir modeling and evaluation [47,48]. It is noted that when classifying different rock types, facies, porosity, and permeability are all considered.…”
Section: Block B30u B27umentioning
confidence: 99%
“…Additionally, the LRP intervals are commonly identified with high water saturation, which makes such intervals of low interest to the extent that they are discarded as attractive to appraise, particularly when oil prices are low. Typically, LRP zones are characterized by formation interval, with moderate to high porosities, showing extremely low resistivity that are often less than 3 X-m and most frequently encountered in areas with saline formation water (Griffiths et al 2006;Obeidi et al 2010;Worthington 2000;Farouk et al 2014;Uchida et al 2015). While Boyd et al (1995) proposed that the resistivity range is between 0.5 and 5 X-m, several other researchers, like Zhao et al (2000), stated that LRP can be identified by the ratio of the pay zone to the water-bearing zone and this ratio is considered to be in the range of 2.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, in carbonate reservoirs, the macropores hold and produce the moveable hydrocarbons due to their lower entry pressure, which is adjacent to micropores holding the immobile highly saline formation water due to the high entry pressure. Such micropores can be present in different forms as highlighted by Uchida et al (2015) and . Hassan and Kerans (2013) investigated the geological consequences of LRP in carbonate reservoirs and reported that the microporosity is 70% of the total porosity in all facies studied from 14 core plugs.…”
Section: Introductionmentioning
confidence: 99%